Mid-Term Outcomes Following Percutaneous Pulmonary Valve Implantation Using the "Folded Melody Valve" Technique. (April 2021) - Jalal, Zakaria; Valdeolmillos, Estíbaliz; Malekzadeh-Milani, Sophie; Eicken, Andreas; Georgiev, Stanimir; Hofbeck, Michael; Sieverding, Ludger; Gewillig, Marc; Ovaert, Caroline; Bouvaist, Helene; Pillois, Xavier; Thambo, Jean-Benoit; et al.
Abstract : Background: The folded valve is a manual shortening of the Melody device, which has been validated as a valuable therapeutic option for the management of dysfunctional right ventricular outflow tracts needing a short valved stent. In this article, we aimed to evaluate, in a multicenter cohort, the mid-term outcomes of patients in whom a percutaneous pulmonary valve implantation was performed using the folded valve technique. Methods: A 2012 to 2018 retrospective multicenter study was performed in 7 European institutions. All patients who benefit from percutaneous pulmonary valve implantation with a folded Melody valve were included. Results: A total of 49 patients (median age, 19 years [range 4–56], 63% male) were included. The primary percutaneous pulmonary valve implantation indication was right ventricular outflow tract stenosis (n=19; 39%), patched native right ventricular outflow tracts were the most common substrate (n=15; 31%). The folded technique was mostly used in short right ventricular outflow tracts (n=28; 57%). Procedural success was 100%. After a median follow-up of 28 months (range, 4–80), folded Melody valve function was comparable to the immediate postimplantation period (mean transvalvular peak velocity=2.6±0.6 versus 2.4±0.6 m/s, P >0.1; only 2 patients had mild pulmonary regurgitation). Incidence rate of valve-related reinterventions was 2.1% per person per year (95% CI, 0.1%–3.9%). The probability of survival without valve-related reinterventions at 36 months was 90% (95% CI, 76%–100%). Conclusions: The folded Melody valve is a safe technique with favorable mid-term outcomes up to 6.5 years after implantation, comparable with the usual Melody valve implantation procedure. Complications and reinterventions rates were low, making this technique relevant in selected patients.